APLIKASI PENDEKATAN HIGH TECHNOLOGY PADA SPORT CENTER DI KABUPATEN ENREKANG - Ardiansyah, Muhammad; Nursyam, Nursyam; Rahim, Rahmiani (TIMPALAJA : Architecture Student Journals, 2026)
Enrekang Regency has a strong public interest in sports; however, the availability of representative sports facilities and infrastructure remains limited. This condition indicates the need for a Sport Center as an integrated facility that can accommodate sports, recreation, and social interaction activities. This study aims to design a Sport Center in Enrekang Regency using the High Technology Architecture approach to create a functional, modern sports facility with a strong visual character. The method used in this study is a descriptive, qualitative, architectural design approach, carried out through site surveys, literature and precedent studies, and interviews with relevant stakeholders. The collected data were analyzed to formulate a design concept based on user needs, site conditions, sports facility standards, and the principles of High Technology Architecture. The design results show that the application of the high-tech concept is evident in the use of smart glass, solar panels, lightweight space-frame structures, and building forms that emphasize transparency, modernity, and a futuristic image. In addition to the main building, the design includes supporting facilities such as a lobby, food court, retail shop, communal space, an outdoor sports field, and a parking area. Therefore, the proposed Sport Center is expected to become a representative sports facility that supports community activities and serves as a new architectural landmark in Enrekang Regency.